INTEGRASI NILAI-NILAI KEISLAMAN DALAM PEMBELAJARAN IPS PADA KURIKULUM 2013 - Amirah Al May Azizah (Universitas Islam Malang, 2021)
Islamic values are needed in education. Islamic values in social studies learning at MI are manifested in the overall social studies learning pattern by paying attention to the existence of social studies learning as a general science and paying attention to the Islamic values of students to shape the character of students. This writing aims to determine the Islamic value integrated with general subjects, especially social science (IPS) in class III MIM Bendo PK Nogosari, and Islamic education based on scientific integration between general science (academic) and religious science (non-academic). This research uses qualitative research. This research uses observation, documentation and interview techniques. Material on the basic competencies of social science class III at MIM Bendo PK Nogosari can be integrated with Islamic values, for example material about the appearance of nature in class III, educators invite students to be more grateful because in this case they can see and enjoy Allah SWT's creation which also inserts Thayyibah sentence according to his feelings. In addition, the values that can be taken in this natural appearance material are the value of gratitude. Then the material for associating with neighbors which includes morals in socializing with other humans has also been explained in Q.S Luqman verse 18. There are still many other materials in the basic competences of class III social studies that can be integrated with Islamic values.